Near-Complete Genome Sequence of Feline Immunodeficiency Virus from Colombia - Taniwaki, Sueli A.; Jimenez-Villegas, Tatiana; Santana-Clavijo, Nelson F.; Cruz, Tais F. [UNESP]; Silva, Sheila O. S.; Valencia-Bacca, Juan D.; Loaiza-Pedreros, Felipe; Richtzenhain, Leonardo J.; Ferreira, Fernando; Araujo Junior, Joao P. [UNESP]; Brandao, Paulo E. (Amer Soc Microbiology, 2020)
Feline immunodeficiency virus (FIV) is an important pathogen of domestic and wild felids. Although serological tests suggest the presence of FIV in cats from Colombia, no molecular characterization has been reported. Here, we describe the near-complete genome of FIV subtype A from a Colombian domestic cat.